Kesiapan Kerja di Era Digital Fatigue : Analisis Peran Efikasi Diri, Kecerdasan Emosional, dan Keterampilan Digital - Fata A’A Rahman Aryanto; Pradita Nindya Aryandha (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study examines the impact of self-efficacy, emotional intelligence, and digital skills on student job readiness in the era of digital fatigue. This study used a descriptive method and involved 202 students from Subang studying in the Special Region of Yogyakarta (DIY), selected using a purposive sampling technique. Data were collected through an online questionnaire and analyzed using multiple linear regression with the help of SPSS. The results show that self-confidence, emotional intelligence, and digital skills each have a positive and significant impact on job readiness, and together increase students' adaptability and resilience in the era digital fatigue. These findings emphasize the importance of building self-confidence, managing emotions, and mastering digital skills to mitigate the impact of digital fatigue and prepare students for increasingly competitive and modern job markets. The results of this study can serve as a reference for students, lecturers, and policymakers in developing strategies that combine mental readiness and mastery of digital skills in the educational process at universities. This study examines the impact of self-efficacy, emotional intelligence, and digital skills on student job readiness in the era of digital fatigue. This study used a descriptive method and involved 202 students from Subang studying in the Special Region of Yogyakarta (DIY), selected using a purposive sampling technique. Data were collected through an online questionnaire and analyzed using multiple linear regression with the help of SPSS. The results show that self-confidence, emotional intelligence, and digital skills each have a positive and significant impact on job readiness, and together increase students' adaptability and resilience in the era digital fatigue. These findings emphasize the importance of building self-confidence, managing emotions, and mastering digital skills to mitigate the impact of digital fatigue and prepare students for increasingly competitive and modern job markets. The results of this study can serve as a reference for students, lecturers, and policymakers in developing strategies that combine mental readiness and mastery of digital skills in the educational process at universities.